2022
DOI: 10.3390/ijms232314751
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Combination of Ascorbic and Ellagic Acids in Sperm Oxidative Damage Inhibition

Abstract: It is known that an altered redox balance interferes with normal spermatic functions. Exposure to genotoxic substances capable of producing oxidative stress (OS) can cause infertility in humans. The use of antioxidants to reduce oxidative stress contributes to the improvement in reproductive function. This study focused on an antigenotoxic evaluation of ellagic acid (EA) and ascorbic acid (AA) in combination against benzene genotoxic action on human spermatozoa in vitro. In addition to the evaluation of sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Different observations in the sensitivity of sperm to oxidative stress may be due to differences in experimental methodology and animal species. search of Mottola et al (2022) on human sperm, where EA did not cause any changes in sperm parameters. The effects of EA on the kinematic parameters were not significant (P > 0.05).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Different observations in the sensitivity of sperm to oxidative stress may be due to differences in experimental methodology and animal species. search of Mottola et al (2022) on human sperm, where EA did not cause any changes in sperm parameters. The effects of EA on the kinematic parameters were not significant (P > 0.05).…”
Section: Discussionmentioning
confidence: 85%
“…As far as we know, several studies have been conducted using ellagic acid as a supplement to the sperm of different animal species and humans (Omur and Coyan 2016;Kia et al 2017;Bucak et al 2019;Najafi et al 2019;Mottola et al 2022). We observed that the values of total and progressive sperm motility did not change after the addition of EA to sperm, which is consistent with the re-apoptotic spermatozoa (Yo-Pro-1+), acrosome integrity (PNA+), mitochondrial activity (MT Green+), and ROS production (CellRox+).…”
Section: Discussionmentioning
confidence: 99%
“…In physiological concentrations, ROS are necessary for proper spermatic functions such as the acrosome reaction, capacitation, and sperm-oocyte fusion [1]. However, an excess of ROS leads to OS, causing structural and functional damage to sperm cells, including lipid peroxidation, protein oxidation, and DNA damage, resulting in compromised male fertility and a risk of genetic mutations in offspring [2,3]. Elevated ROS concentrations, found in seminal fluid samples from infertile men, are often due to pathological conditions or environmental factors such as infections, smoking, alcoholism, and diet [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Ten published manuscripts, including seven research articles and three reviews, can be found in this Special Issue. Two articles [ 1 , 2 ] underline the importance of the redox balance in sperm functions. Mottola et al [ 1 ] report for the first time the antigenotoxic effects of the combined exposure to ascorbic and ellagic acids, two well-known antioxidants, on human spermatozoa in vitro.…”
mentioning
confidence: 99%
“…Two articles [ 1 , 2 ] underline the importance of the redox balance in sperm functions. Mottola et al [ 1 ] report for the first time the antigenotoxic effects of the combined exposure to ascorbic and ellagic acids, two well-known antioxidants, on human spermatozoa in vitro. The authors demonstrated that the combination of the two antioxidants generates a time-dependent antigenotoxic action against benzene, reducing both the sperm DNA fragmentation index and oxidative stress, putting the foundations for clinical studies on the use of these class of antioxidants as a therapy for male infertility.…”
mentioning
confidence: 99%